Enhancing Speaking Skill through Storytelling: A Narrative Inquiry Study - Arifatin, Fais Wahidatul (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2026)
Speaking is a fundamental component of English language learning, yet many EFL learners continue to struggle with anxiety, lack of confidence, and limited opportunities for authentic communication. This narrative inquiry study explored how storytelling enhances students’ speaking skills by examining the lived experiences of three high school students who participated in a storytelling competition at Universitas Muhammadiyah Lamongan. Data were collected through semi-structured interviews, observations, and reflective journals, then analyzed using thematic narrative analysis. The findings reveal three major themes: (1) increased confidence and reduced speaking anxiety, (2) development of fluency and vocabulary use, and (3) storytelling as a meaningful and enjoyable learning experience. Storytelling was found to provide a supportive and engaging environment that encourages natural and meaningful communication. It allows learners to connect personal experiences with linguistic expression, fostering emotional engagement and intrinsic motivation. The study concludes that storytelling is a powerful pedagogical strategy for enhancing speaking skills in EFL contexts, promoting communicative fluency, confidence, and learner autonomy. Teachers are encouraged to incorporate storytelling to create authentic, reflective, and learner-centered speaking instruction.